Answer:
Q7. 945; Q8. 45 927; Q9. 546.75
Explanation:
7. Arithmetic sequence
The explicit formula for the nth term of an arithmetic sequence is
aₙ = a₁ + d(n - 1 )
a₁ is the first term, and d is the difference in value between consecutive terms. Thus,
a₁ = 91, d = -4, n = 15
a₁₅ = 91 - 4(15 - 1) = 91 - 4(14) = 91 - 56 = 35
We find the sum of an arithmetic series by multiplying the number of terms by the average of the first and last terms.
S = n[(a₁ + a₁₅)/2]
S = 15[(91 + 35)/2] = 15 × 126/2 = 945
The sum of the first 15 terms is 945.
8. nth term of geometric sequence
a₃ = 63 and r = -3
The explicit formula for the nth term of a geometric sequence is
aₙ = a₁rⁿ⁻¹
a₁ is the first term and r is the common ratio.
If we start counting from a₃, then a₉ is the seventh term in the sequence.
In your sequence, r = -3.
a₇ = 63(-3)⁷⁻¹ = 63(-3)⁶ = 63 × 729 = 45 927
The ninth term in the sequence is 45 927.
9. Sum of geometric series
a₁ = 729, aₙ = -3, r = -⅓
I don't know what you mean by aₙ = -3. It says that every term is -3, so I am going to ignore it.
Since |r| <1, we have a convergent series, and the formula for the sum is
S = a₁/(1 - r)
∴ S = 729/[(1 - (-⅓)] = 729/1⅓ = 729/(⁴/₃) = 729 × ¾ = 546.75
The sum of the geometric series is 546.75.